Konsep Ekonomi Ibnu Khaldun Dan Relevansinya Dengan Teori Ekonomi Modern (Studi Analisis Konsep Ekonomi Dalam Kitab Muqaddimah) - Khairil Henry (AL-FIKRA, 2020)
Ibn Khaldun is an Islamic scientist who through his book entitled "muqadimah" has become an intellectual bridge for the development of science. He has provided facilities for intellectual leap in scientific development. He has examined several problems and phenomena of life about society, history and economics that have never been studied by scientists before.He has introduced new scientific concepts with a high degree of originality and laid the foundations of thought and theory for subsequent scientists. Ibn Khaldun had become one of the earliest and most well-known theorists in sociology, history and economics. He has become the founder of a school of thought which is only worthy named after his own name. In the book of Muqaddimah, we can get Ibn Khaldun's method in explaining various economic problems and linking these economic problems with the verses contained in the Qur'an. This is evidence of his efforts to explain that various economic activities have actually been regulated in Islam. His thinking deserves to be a reference in studying especially economics which has always been dominated by Western scientists. Keywords: Ibn Khaldun, Muqaddimah, Economics